Influenza vaccines really work? Keeping apart the true from the false - Nguyen-Van-Tam, Jonathan; Gross, Diane; Sturkenboom, Miriam; Parrish-Sprowl, John (Elsevier, 2015)
A yearly seasonal flu vaccine is the best preventive method we have against influenza at this time. Even then, vaccination adoption is hampered by on-going discussions about safety and effectiveness. In order to dot the I's and cross the T's at the fifth ESWI influenza conference, a dedicated SPI track focused on these important aspects of influenza vaccination.